Variation in Symmetry Around Doped Nd3+ Ion in Saturated Solution of Sulphonalides with Reference to Judd-Ofelt Electronic Spectral Parameter - Tater, P.C.; Aryamitra Pandey, Ms.; Soni, K.P. (Asian Journal of Chemistry, 2010)
Three sulphonanilides have been synthesised. A comparative electronic-spectral characterization of Nd3+ doped sulphonanilide solutions has been done on the basis of Slater-Condon, Judd-OfeIt and Lande theories. The involvement of 4f-orbitals in Nd3+ doped systems including deviation in symmetry has been discussed.